The study of customer satisfaction towards Tabung Haji Travel and Services (Kuala Lumpur Branch) / Mohamad Taufiq Mohamad - Mohamad, Mohamad Taufiq (Faculty of Business and Management, 2009)
This study is a research of customer satisfaction towards Tabung Haji Travel and Services in Kuala Lumpur Branch (THTS) whereby the researcher was in internship in the organization for five months to complete the study in Bachelor of Administration (Hons) Marketing. The research is about the satisfactory of the customers towards the organization who were using the Haj and Umrah services. Furthermore, this research explained the relationship between the independent variables and dependent variable which related to one and another. The independent variables consist of price, product, advertising, technology and service quality has connected with the dependent variable which is the customers’ satisfaction. The customers’ satisfaction may be affected if any modifications have been made on those independent variables due to their linkage to each other and may influence the organization performance and services in tourism industry. The results of this research are based on the findings and analysis made using the Statistical Package for the Social Science Program (SPSS) and illustrates the verification between the dependent variable and independent variables. Literature reviews based on varies articles which are relevant to the study are included to verify and sustain that the research is valid. Conclusions and recommendations are comprehended for the organization to develop and improve in the upcoming future.